2010
DOI: 10.1016/j.juro.2010.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Urinary Biomarker Discovery in Ureteropelvic Junction Obstruction: A Proteomic Approach

Abstract: These results confirm the presence of significant differences in the urinary proteome in unilateral ureteropelvic junction obstruction compared to age matched normal individuals. This study adds new information about levels of abundance of specific proteins and peptides in ureteropelvic junction obstruction, which may allow for better classification of disease subgroups and help to establish improved indications for the early selection of surgical candidates based on urinary protein biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…In addition, many proteins that were implicated in obstructive nephropathy in a prior study (8) were also statistically significant in this study, with the same quantitative trends. Elevated proteins included angiotensin; albumin; keratin 8; keratin 9; lectin, galactoside-binding, sol- uble, 3 binding protein; macrophage inhibitory factor; myosin heavy chain 7; serpin peptidase inhibitor; clade A member 1; and transferrin.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In addition, many proteins that were implicated in obstructive nephropathy in a prior study (8) were also statistically significant in this study, with the same quantitative trends. Elevated proteins included angiotensin; albumin; keratin 8; keratin 9; lectin, galactoside-binding, sol- uble, 3 binding protein; macrophage inhibitory factor; myosin heavy chain 7; serpin peptidase inhibitor; clade A member 1; and transferrin.…”
Section: Discussionsupporting
confidence: 80%
“…(5,6,8,12) However, these studies were differently focused, exclusively analyzing the low molecular weight peptidome (Ͻ 10kDa) or had a low degree of proteomic coverage. Points of merit in the current study include: (1) very well defined, age-and sexmatched severe disease and control cohorts (Table I) to provide definitive insight into the pathophysiology of clinically significant renal obstruction; (2) unique access to urine directly from the diseased kidney (KU); and (3) the deepest profiling of the UPJO urinary proteome to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were only 6 children in the study group of children >1 year (5 for operation and 1 no operation), which is a weakness of the study, and it is therefore necessary with further and larger studies to clarify whether age-specific urinary proteome patterns will be able to identify older children requiring pyeloplasty for treatment of UPJO [55]. Mesrobian et al confirmed the presence of significant differences in the urinary proteome in UPJO compared to age-matched normal individuals [56]. Their study comprised 25 newborns presenting with unilateral grade 4 hydronephrosis secondary to UPJO followed for at least 12 months, and a control group of 21 healthy newborns (normal ultrasound).…”
Section: Urinary Proteome Analysismentioning
confidence: 99%
“…Regarding the pediatric nephrourology setting, there have been various attempts to identify noninvasive diagnostic markers of congenital renal obstruction and vesicoureteral reflux (VUR) [14][15][16]. For instance, Furness et al [17] have shown fourfold elevated TGF-β1 levels in children with upper urinary tract obstruction.…”
Section: Introductionmentioning
confidence: 99%